KONSTRUKTIVISME DALAM PEMBELAJARAN SAINS DI SD: TINJAUAN EPISTEMOLOGI, ONTOLOGI, DAN KERAGUAN DALAM PRAKSISNYA - Barlia, Lily (Jurnal Cakrawala Pendidikan, 2015)
Abstract: Constructivism in Science Learning in Elementary Schools: Epistemological and Ontological Perspectives and Doubts in the Praxis. A constructivist perspective focuses on children's contribution to the construction of knowledge. Constructivism believes that a child is a real inquirer and discoverer who is actively engaged in building theories about the world and the way it works without the aid of direct instructions. The implication is that teachers have to give wider mandates to students, to provide them with contexts for experimentation to occur, and to facilitate theory building by providing helpful experiences. Epistemologically and ontologically, there are still doubts about the application in practice. This, however, should not be a constraint for science teachers to implement basic principles of constructivism as one of the alternative solutions to educational reform and movement in the elementary school science. Keywords: constructivism, science learning science, elementary school science